2019
DOI: 10.1038/s41556-019-0304-7
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial proteolytic activity and interaction with non-resorbing osteoclasts mediate bone elongation

Abstract: Growth plate cartilage contributes to the generation of a large variety in shapes and sizes of skeletal elements in the mammalian system. The removal of cartilage and how this process regulates bone shape are not well understood. Here we identify a non-bone-resorbing osteoclast subtype termed vessel associated osteoclast (VAO). Endothelial cells (ECs) at the bone-cartilage interface support VAOs through a RANKL-RANK signaling mechanism. Contrary to classical bone associated osteoclasts (BAOs), VAOs are dispens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
143
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(160 citation statements)
references
References 58 publications
6
143
1
Order By: Relevance
“…(87) Further, PDGFRβ + skeletal stem and progenitor cells (SSPCs) mainly reside in perivascular niches, and PDGF-PDGFRβ signaling induces SSPC proliferation, trafficking, and angiotropism during bone injury. (88) (106) ; Basic-Jukic and colleagues (147) BMP-4 ; Klimiuk and colleagues (142) ; Zimmermann-Geller and colleagues (143) FGF1 (60) ; Dias and colleagues (61) IL-33 Romeo and colleagues (39) Nidogen-1 ; Song and colleagues (38) Tenascin-C Romeo and colleagues (39) TNF-α Carlson and colleagues (182) Vascular roles of fibroblast growth factor Fibroblast growth factors (FGFs) are mainly secreted by bone lineage cells, including chondrocytes and osteoblasts, (89,90) and the receptors FGFR1 and FGFR2 expressed in vascular cells. (91) FGFs induces the expression of multiple angiogenic molecules, including VEGFA and VEGFR2, stimulating the growth of blood vessels and contributing to chondrocyte proliferation and the initiation of chondrocyte hypertrophy.…”
Section: Role Of Vegfa During Bone Developmentmentioning
confidence: 99%
“…(87) Further, PDGFRβ + skeletal stem and progenitor cells (SSPCs) mainly reside in perivascular niches, and PDGF-PDGFRβ signaling induces SSPC proliferation, trafficking, and angiotropism during bone injury. (88) (106) ; Basic-Jukic and colleagues (147) BMP-4 ; Klimiuk and colleagues (142) ; Zimmermann-Geller and colleagues (143) FGF1 (60) ; Dias and colleagues (61) IL-33 Romeo and colleagues (39) Nidogen-1 ; Song and colleagues (38) Tenascin-C Romeo and colleagues (39) TNF-α Carlson and colleagues (182) Vascular roles of fibroblast growth factor Fibroblast growth factors (FGFs) are mainly secreted by bone lineage cells, including chondrocytes and osteoblasts, (89,90) and the receptors FGFR1 and FGFR2 expressed in vascular cells. (91) FGFs induces the expression of multiple angiogenic molecules, including VEGFA and VEGFR2, stimulating the growth of blood vessels and contributing to chondrocyte proliferation and the initiation of chondrocyte hypertrophy.…”
Section: Role Of Vegfa During Bone Developmentmentioning
confidence: 99%
“…Osteoblasts support the vasculature by producing VEGF and basic fibroblast growth factor (bFGF) while endothelial cells (ECs) provide factors that further osteoblast differentiation and activity (17). Furthermore, pre-osteoclasts and non-bone-resorbing osteoclasts have been described to enhance vascularization and osteogenesis in the growth plate area by releasing platelet-derived growth factor-BB (PDGF-BB) or supporting vessel anastomosis (18,19). While the production of angiogenic factors by osteoprogenitors is well-known, there is evidence accumulating that, conversely, endothelial cells can also impact on bone formation, at least during bone development (7).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, researchers have demonstrated that type H vessels may have major effects on bone development and are mostly regulated by PDGF‐BB . Despite their limited quantity, many osteoprogenitor cells remain near type H vessels, and disruption of type H vessels can influence bone growth . Although complete inhibition of osteoclasts can reduce aging‐related bone loss, this strategy ignores the positive role of Trap + preosteoclasts in the coupling of osteogenesis and angiogenesis .…”
Section: Discussionmentioning
confidence: 99%
“…5,7,27 Angiogenesis plays an important role in sustaining the normal bone structure, and osteogenesis is based on the nutrient supply of blood vessels and requires molecular stimulation from endothelial cells. [1][2][3]28,29 The contribution of type H vessels to bone formation has been verified, [1][2][3]5,7,22,30,31 and its quantity is relevant to bone mass. 8 Although we proved that NCF could inhibit osteoclast formation and increase the quantity of Trap + preosteoclasts, the influence of NCF on the function of endothelial cells and the formation of type H vessels was not clear.…”
Section: F I G U R E 4 Ncf Potentiates the Angiogenesis-related Activmentioning
confidence: 91%
See 1 more Smart Citation